Analisis Perbandingan Kinerja Protokol Routing OLSR dan DSDV Pada MANET Berdasarkan Pergerakan Node - Brillian Taufan; Rakhmadhany Primananda; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mobile adhoc Network is a wireless network consisting of nodes, node itself tend to move freely or mobililize without any infrastructure such as router. In an adhoc network, the nodes works as router itself which responsible for finding and handling paths to each destination node in a network (Wijayanto, 2009). To set the entire routing process, the MANET network topology does not require a router, because each device functions as a router to determine the path to be passed. There is a proactive routing protocol used in MANET, there are OLSR (Optimized Link State Routing) and DSDV (Destination Sequenced Distance Vector). OLSR and DSDV is used in this study because it includes proactive routing protocols that can adapt quickly to dynamic link conditions. This study provides an analysis of the effect of proactive protocol performance based on the movement of nodes in the MANET topology using Network Simulator 3.25. in this study, the movements used Random Waypoint and Random Direction by measuring network performance using test parameters in the form of average end-to-end delay, packet delivery ratio (PDR), and Overhead Routing. Tests carried out on both proactive protocols, namely OLSR and DSDV with test scenarios in the form of variations in the number of nodes as much as 20,30,40 and 50 nodes, simulation area of 200 m2, 500m2, 800 m2 and 1000 m2, and mobility modes Random Waypoint and Random Direction. The result of each performance from the average end to end delay DSDV protocol is better than the OLSR protocol. This is indicated by the average end to end delay value of the DSDV protocol, which is 0.00107591ms. But on the results of measurement of packet delivery ratio (PDR) and routing overhead OLSR is better than DSDV because OLSR has an MPRs mechanism (Multi point relays), MPR can reduce the number of broadcast information messages that have the same information and to reduce routing overhead